Simultaneous Enrichment and On-line Detection of Low-Concentration Copper, Cobalt, and Nickel Ions in Water by Near-Infrared Diffuse Reflectance Spectroscopy Combined with Chemometrics. (22nd November 2019) - Iqbal, Jibran; Du, Yiping; Howari, Fares; Bataineh, Mahmoud; Muhammad, Nawshad; Rahim, Abdur
Abstract: Sensitive detection of heavy metal ions in water is of great importance considering the effects that heavy metals have on public health. A developed fluidized bed enrichment technique was used to concentrate and detect low concentrations of Cu 2+, Co 2+, and Ni 2+ in water samples by near-IR diffuse reflectance (NIDR) spectroscopy (NIDRS) directly without using any chemicals or reagents. The NIDR spectraof adsorbent were measured on-line, and quantitative detection was achieved by applying a built partial least-squares chemometric model. Sensitivity and accuracy was improved significantly because large-volume mixture solutions were used in the enrichment process. Root mean square error of cross-validation values for Cu 2+, Co 2+, and Ni 2+ were 0.29, 0.41, and 0.35 μg/mL, respectively, with mean relative error values in the acceptable range of 6.56–10.27%. This study confirms the potential application of fluidized bed enrichment combined with NIDRS and chemometrics for the simultaneous detection of trace heavy metal ions in water, with low relative error.